2013
DOI: 10.1371/journal.pone.0071448
|View full text |Cite
|
Sign up to set email alerts
|

No Control Genes Required: Bayesian Analysis of qRT-PCR Data

Abstract: BackgroundModel-based analysis of data from quantitative reverse-transcription PCR (qRT-PCR) is potentially more powerful and versatile than traditional methods. Yet existing model-based approaches cannot properly deal with the higher sampling variances associated with low-abundant targets, nor do they provide a natural way to incorporate assumptions about the stability of control genes directly into the model-fitting process.ResultsIn our method, raw qPCR data are represented as molecule counts, and described… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
154
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(157 citation statements)
references
References 34 publications
0
154
0
Order By: Relevance
“…Statistical analysis of qPCR data was performed using the MCMC.qpcr R package (Matz et al, 2013; R Core Team, 2014) in the ”classic” mode, which uses a normalization procedure relative to ”control” genes. The following control genes were used to normalize the qPCR expression values in the radial nerve cord dataset: elongation factor 2 (EF2) , ribosomal protein rpL18a , Mn-superoxide dismutase (Sod) , and V-type proton AT-Pase 16 kDa proteolipid subunit (ATP6L).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Statistical analysis of qPCR data was performed using the MCMC.qpcr R package (Matz et al, 2013; R Core Team, 2014) in the ”classic” mode, which uses a normalization procedure relative to ”control” genes. The following control genes were used to normalize the qPCR expression values in the radial nerve cord dataset: elongation factor 2 (EF2) , ribosomal protein rpL18a , Mn-superoxide dismutase (Sod) , and V-type proton AT-Pase 16 kDa proteolipid subunit (ATP6L).…”
Section: Methodsmentioning
confidence: 99%
“…∗ P < 0.05, ∗∗∗ P < 0.001. The full output of the MCMC.qpcr R package (Matz et al, 2013) containing relative expression values and corresponding p-values can be found in Electronic Supplementary Material, Text S3, and Text S4…”
Section: Figmentioning
confidence: 99%
“…There is a premise that reference genes cannot be regulated by the experimental conditions of the sample set (Robledo et al 2014). The geNorm and BestKeeper algorithms are based on the assumption that none of the analyzed genes are co-regulated (Matz et al 2013). For this reason, the use of more than one algorithm for the validation of reference genes is suggested to give more reliable results (Zyzynska-Granica and Koziak 2012).…”
Section: Expression Stability Of Reference Genesmentioning
confidence: 99%
“…All raw CT microRNA and mRNA data were normalized within sex to the median of the DMSO P15 group in an R statistical package for qPCR analysis which utilized a generalized linear mixed model with Poisson-lognormal errors and a Bayesian Marco Chain Monte Carlo sampling scheme (47). All data were normally distributed and homoscedastic.…”
Section: Methodsmentioning
confidence: 99%